Asean Guidelines for Special Economic Zones (SEZs) Development and Collaboration: A Study of SEZ Arun Lhokseumawe, Aceh- Indonesia - M Yakub Aiyub Kadir; Azhari; Teuku Haflisyah; Sufyan; Eka Kurniasari (JURNAL MERCATORIA, 2022)
The establishment of Special Economic Zones (SEZ) Lhokseumawe, Aceh province in 2017, has   accelerated economic development in post-conflict situation in Aceh province, Indonesia. This area is supported by the existence of former Arun gas industry facilities which was ended in 2014. This paper investigates the meaning, the extent to which the Asean Guidelines for SEZ has been applied and contributed to accelerate investment in SEZ Arun Lhokseumawe, along with progresses and challenges ahead. This is essential for sustainable peace post peace agreement(MoU) Helsinki.  Using doctrinal approach and secondary data, this paper found that SEZ Arun Lhokseumawe has partly adopted the Asean Guideline for SEZ, in terms of a clear development strategy, clarification and separation of roles and responsibility, delegation of authority, building strong institutional capacities, and increasing Asean SEZ cooperation. Therefore, little progress of this SEZ become questionable. Current constraint of asset ownership, the absence of independent management has advised to have Aceh Qanun on the Administrator Institution of the SEZ Arun Lhokseumawe. The Qanun is expected to become a legal umbrella and technical guidance in the effective management of the SEZ Arun Lhokseumawe.